2010
DOI: 10.1186/cc8992
|View full text |Cite
|
Sign up to set email alerts
|

4G/5G polymorphism of PAI-1 gene is associated with multiple organ dysfunction and septic shock in pneumonia induced severe sepsis: prospective, observational, genetic study

Abstract: IntroductionActivation of inflammation and coagulation are closely related and mutually interdependent in sepsis. The acute-phase protein, plasminogen activator inhibitor-1 (PAI-1) is a key element in the inhibition of fibrinolysis. Elevated levels of PAI-1 have been related to worse outcome in pneumonia. We aimed to evaluate the effect of functionally relevant 4G/5G polymorphism of PAI-1 gene in pneumonia induced sepsis.MethodsWe enrolled 208 Caucasian patients with severe sepsis due to pneumonia admitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 39 publications
(44 reference statements)
0
34
0
2
Order By: Relevance
“…Hypoxemia, which functions as a stressor, increases the expression of heat-shock proteins, and protects important organs, such as the lungs and the brain, from harm. Previous studies (Sapru et al, 2009;Madách et al, 2010) have reported a correlation between the 4G/5G polymorphism in the plasminogen activator inhibitor-1 (PAI-1) gene, and the level of expression of pulmonary edema fluid and PAI-1 in the plasma after lung injury. Patients who express the 4G/4G and 4G/5G genotype showed a significant increase in PAI-1 expression; such patients suffered illnesses and inflammatory reactions of greater intensity, and demonstrated obvious pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxemia, which functions as a stressor, increases the expression of heat-shock proteins, and protects important organs, such as the lungs and the brain, from harm. Previous studies (Sapru et al, 2009;Madách et al, 2010) have reported a correlation between the 4G/5G polymorphism in the plasminogen activator inhibitor-1 (PAI-1) gene, and the level of expression of pulmonary edema fluid and PAI-1 in the plasma after lung injury. Patients who express the 4G/4G and 4G/5G genotype showed a significant increase in PAI-1 expression; such patients suffered illnesses and inflammatory reactions of greater intensity, and demonstrated obvious pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
“…Решение о начале ЗПТ следует принимать на основе оценки динамики лабораторных данных и всесто-роннего анализа клинической ситуации [19].…”
Section: Discussionunclassified
“…Also, García-Segarra et al [30] found more severe organ dysfunction in association with higher plasma PAI-1 concentrations and a twofold increase in mortality among patients with septic shock who were homozygous for the 4G deletion polymorphism of PAI-1 . Recently, Madách et al [31] performed a cohort study of 208 Caucasian patients with severe sepsis due to pneumonia and found that those with the 4G/4G and 4G/5G genotypes of PAI-1 had a 2.74-fold higher risk of multiple organ dysfunction syndrome and a 2.57-fold higher risk of septic shock than those with 5G/5G. Multivariate analysis with adjustment for independent predictors (such as age, nosocomial pneumonia and positive culture) also indicated that carriers of the 4G allele had a higher prevalence of multiple organ dysfunction syndrome [31].…”
Section: Discussionmentioning
confidence: 99%